PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PERWAKILAN BANK INDONESIA PROVINSI GORONTALO - Suaiba, Haidar Rizki; Abdullah, Julie; Suyanto, Moh. Afan; Karundeng, Deby Rita (2021)
This study aims to determine and analyze the influence of organizational culture on employee performance, the influence of motivation on employee performance, the influence of the work environment on employee performance and the influence of organizational culture, motivation and work environment on employee performance at the Bank Indonesia representative office Gorontalo.The population that is used as the research target is the parties related to the employee's performance as many as 42 people, and all of them become respondents using multiple linear regression analysis models.Based on the results of statistical analysis through the SPSS Program, it shows that together the three independent variables, namely: organizational culture, motivation and work environment have a positive and significant influence on employee performance While partially it is found that the work environment has a dominant significant influence on employee performance at the Bank Indonesia representative office Gorontalo.